Discover a world of knowledge at Westonci.ca, where experts and enthusiasts come together to answer your questions. Ask your questions and receive accurate answers from professionals with extensive experience in various fields on our platform. Join our platform to connect with experts ready to provide precise answers to your questions in different areas.
Sagot :
To solve the equation [tex]\(\left(\frac{1}{4}\right)^{3z-1} = 16^{z+2} \cdot 64^{z-2}\)[/tex], let's proceed through the following steps:
1. Rewrite all terms with the same base:
- Notice that [tex]\(\frac{1}{4} = 4^{-1}\)[/tex].
- Note that [tex]\(16 = 4^2\)[/tex].
- Also, [tex]\(64 = 4^3\)[/tex].
Thus, we can rewrite the original equation:
[tex]\[ \left(4^{-1}\right)^{3z-1} = \left(4^2\right)^{z+2} \cdot \left(4^3\right)^{z-2} \][/tex]
2. Simplify the exponents using properties of exponents:
- For the left-hand side:
[tex]\[ \left(4^{-1}\right)^{3z-1} = 4^{(-1)(3z-1)} = 4^{-(3z-1)} \][/tex]
- For the right-hand side:
[tex]\[ \left(4^2\right)^{z+2} = 4^{2(z+2)} = 4^{2z+4} \][/tex]
[tex]\[ \left(4^3\right)^{z-2} = 4^{3(z-2)} = 4^{3z-6} \][/tex]
- Combining exponents when the bases are the same on the right-hand side:
[tex]\[ 4^{2z+4} \cdot 4^{3z-6} = 4^{(2z+4) + (3z-6)} = 4^{2z + 4 + 3z - 6} = 4^{5z - 2} \][/tex]
Thus, the equation simplifies to:
[tex]\[ 4^{-(3z-1)} = 4^{5z-2} \][/tex]
3. Set the exponents equal to each other:
Since the bases are the same and the equation holds, we can set the exponents equal:
[tex]\[ -(3z-1) = 5z-2 \][/tex]
4. Solve the resulting equation:
[tex]\[ -(3z-1) = 5z-2 \][/tex]
Distribute the negative sign:
[tex]\[ -3z + 1 = 5z - 2 \][/tex]
Combine like terms by adding [tex]\(3z\)[/tex] to both sides:
[tex]\[ 1 = 8z - 2 \][/tex]
Add 2 to both sides to isolate terms involving [tex]\(z\)[/tex]:
[tex]\[ 3 = 8z \][/tex]
Divide by 8:
[tex]\[ z = \frac{3}{8} \][/tex]
Therefore, the solution to the equation [tex]\(\left(\frac{1}{4}\right)^{3z-1} = 16^{z+2} \cdot 64^{z-2}\)[/tex] is:
[tex]\[ z = \frac{3}{8} \][/tex]
1. Rewrite all terms with the same base:
- Notice that [tex]\(\frac{1}{4} = 4^{-1}\)[/tex].
- Note that [tex]\(16 = 4^2\)[/tex].
- Also, [tex]\(64 = 4^3\)[/tex].
Thus, we can rewrite the original equation:
[tex]\[ \left(4^{-1}\right)^{3z-1} = \left(4^2\right)^{z+2} \cdot \left(4^3\right)^{z-2} \][/tex]
2. Simplify the exponents using properties of exponents:
- For the left-hand side:
[tex]\[ \left(4^{-1}\right)^{3z-1} = 4^{(-1)(3z-1)} = 4^{-(3z-1)} \][/tex]
- For the right-hand side:
[tex]\[ \left(4^2\right)^{z+2} = 4^{2(z+2)} = 4^{2z+4} \][/tex]
[tex]\[ \left(4^3\right)^{z-2} = 4^{3(z-2)} = 4^{3z-6} \][/tex]
- Combining exponents when the bases are the same on the right-hand side:
[tex]\[ 4^{2z+4} \cdot 4^{3z-6} = 4^{(2z+4) + (3z-6)} = 4^{2z + 4 + 3z - 6} = 4^{5z - 2} \][/tex]
Thus, the equation simplifies to:
[tex]\[ 4^{-(3z-1)} = 4^{5z-2} \][/tex]
3. Set the exponents equal to each other:
Since the bases are the same and the equation holds, we can set the exponents equal:
[tex]\[ -(3z-1) = 5z-2 \][/tex]
4. Solve the resulting equation:
[tex]\[ -(3z-1) = 5z-2 \][/tex]
Distribute the negative sign:
[tex]\[ -3z + 1 = 5z - 2 \][/tex]
Combine like terms by adding [tex]\(3z\)[/tex] to both sides:
[tex]\[ 1 = 8z - 2 \][/tex]
Add 2 to both sides to isolate terms involving [tex]\(z\)[/tex]:
[tex]\[ 3 = 8z \][/tex]
Divide by 8:
[tex]\[ z = \frac{3}{8} \][/tex]
Therefore, the solution to the equation [tex]\(\left(\frac{1}{4}\right)^{3z-1} = 16^{z+2} \cdot 64^{z-2}\)[/tex] is:
[tex]\[ z = \frac{3}{8} \][/tex]
We hope you found this helpful. Feel free to come back anytime for more accurate answers and updated information. We hope you found what you were looking for. Feel free to revisit us for more answers and updated information. Keep exploring Westonci.ca for more insightful answers to your questions. We're here to help.